PROSES PENGOLAHAN SUSU ULTRA HIGH TEMPERATURE (UHT) BESERTA KEMASAN YANG BERPENGARUH TERHADAP MASA SIMPAN - Jumiono, Aji; Iko Anggara, Putra (Jurnal Ilmiah Pangan Halal, 2021)
Milk is in great demand by the public, pure milk comes from livestock such as cows and goats. People prefer to consume whole milk rather than powdered milk because it is practical to consume. Milk itself cannot be separated from everyday life because of its many benefits. Dairy products, such as powdered milk for babies, UHT liquid milk, etc., are a great opportunity for the advancement of today's business sector. The nutritional content of milk is very high, such as phosphorus, calcium, vitamin A, vitamin B and riboflavin. Fresh milk also still contains some bacteria such as Lactobacillus, streptococcus, leuconostoc and pediocossus. So we need an appropriate handling process where milk can be consumed safely and still get the benefits contained in the milk. The technique of preserving foodstuffs that cannot withstand high temperatures is pasteurization. Various pasteurization methods such as HTST/High Temperature Short Time, LTLT/Low Temperature Long Time, UHT/Ultra High Temperature aim to maintain milk quality and extend shelf life. The provisions governing the quality requirements of UHT milk are contained in SNI 3950:2014.